Formation of communicative competence of linguist students in the process of studying - N. Voloskova; I. Reshetova (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the study of the formation of professional communicative competence of students of linguistic specialties. The main approaches to the study of communicative competence and its components are revealed. Approaches to the definition of this concept are described, the main differences between them are indicated. A diagnostic study aimed at studying the formation of communicative competence was carried out. After analyzing the results of the study we came to the conclusion that the effectiveness of teaching linguistic students and developing their communicative competence within the framework of the disciplines of the curriculum is quite high.